Toxic megacolon: a rare presentation of complicated diverticular disease - Lastra Santiago, Maria Alejandra; Fernández, José Luis Ortiz; Hernández, Daniel Herrera; Payan, Emilio Zevada; Flores, Jimena Celeste Treviño; Gutiérrez, Carlos Andrés Villamar; García, Pablo Patricio Flores; Garcia, Angeles Yasunari Cortes; Sabori, Alejandro Aguilar; Cruz, Erick Antonio García (International Surgery Journal, 2025)
Toxic megacolon is a life-threatening complication most commonly associated with inflammatory bowel disease (IBD) or Clostridioides difficile infection. Its occurrence secondary to complicated diverticular disease is exceedingly rare. We present the case of a 56-year-old woman who developed toxic megacolon in the context of sigmoid diverticular disease. She initially received intravenous antibiotics for Hinchey IB diverticulitis and was discharged on oral therapy. Four days later, she returned with abdominal distension, severe leukocytosis, and radiographic evidence of colonic dilatation and pneumatosis. Emergency surgery revealed a perforated stenotic sigmoid tumor with ischemic changes, and a subtotal colectomy was performed. Histopathological analysis confirmed ischemic colitis with features of toxic megacolon. The patient had an uneventful recovery and was discharged on postoperative day seven. Although toxic megacolon is classically linked to IBD and C. difficile, clinicians must be aware of rare etiologies such as complicated diverticular disease. Prompt recognition and early surgical intervention are crucial for favorable outcomes in atypical presentations.